MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK MELALUI MEDIA KARTU ANGKA PADA ANAK KELOMPOK A TK ISLAM AL-IKHLAS BAGANSIAPIAPI - Herfina Herfina; Zulkifli N Zulkifli N; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Upgrading Know Emblem Card Numbers Through Media Figures on children 4-5 years of age TK Islam Al-Ikhlas Bagansiapiapi. School Year 2013/2014. The background of this study is the lack of increase in the ability of children to recognize the symbol of the number of children aged 4-5 years. Some children can not even mention the epitome of numbers 1 to 10 and have not been able to recognize numbers 1 to 10. Therefore, it is necessary efforts to improve the ability to know the numbers by using the media emblem Score Card. The purpose of this study was to determine whether there is an increased ability to recognize the emblem number of children aged 4-5 years through the media card number provided. This research is a classroom action research conducted in two cycles. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 10 children consisting of 3 girls and 7 boys. Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 22.92% the first cycle to the second cycle of 54.17%, and increased from the prior cycle to cycle II of 77.08%. From the results of these studies concluded that through the ability to recognize the emblem of numbers with a media card numbers can improve the ability to recognize the symbol of the number of children aged 4-5 years in group A TK Islam Al-Ikhlas Bagansiapiapi.Keywords: Coat Numbers, Childhood, Score Card